Gender differences in wildlife-dependent recreation on public lands - Rizzolo, Jessica Bell; Delie, Jackie; Carlson, Shelby C.; Dietsch, Alia M. (Frontiers in Conservation Science, 2023)
Different groups of people may desire and respond to social and ecological conditions in myriad ways (e.g., increased engagement, avoidance). Thus, managers of nature-based recreation sites open for public use (i.e., “public lands”) would benefit from understanding how people with different lived experiences respond under new conditions brought about by regulatory changes (e.g., infrastructural improvements, reduction of access) or environmental changes (e.g., drought, population declines). From a survey of visitors to public lands, specifically National Wildlife Refuges (i.e., refuges) in the United States, we examine gender differences in (a) participation in wildlife-dependent recreation, (b) visitor experiences, and (c) the effect of regulatory and environmental changes on future participation in preferred activities. Our sample (n = 9,918; 40% who self-selected female) included visitors to 69 refuges during 2018 and 2019. Results indicated that people who self-selected female were more likely to indicate that they don’t like being in nature by themselves, and that people close to them enjoy nature-based recreation. People who self-selected female were less likely to engage in hunting or fishing as their primary activity and noted that regulatory changes supporting these activities (specifically, fewer regulations on fishing, fewer regulations on hunting, and more acreage open to fishing/hunting) could decrease their future participation in their primary activity. Thus, respondents who self-selected female may be displaced or alienated from visiting a site if consumptive activities (e.g., hunting) are prioritized as regulatory mechanisms (e.g., for controlling abundant wildlife populations). Adaptive processes that anticipate - in advance of decisions being made - the potential ramifications of regulations on different subgroups of visitors to public lands can identify differential and inequitable impacts, and thus lead to inclusive management decisions when those impacts are preemptively addressed.